2016
DOI: 10.1007/s11356-016-6817-8
|View full text |Cite
|
Sign up to set email alerts
|

Seafood consumption among Chinese coastal residents and health risk assessment of heavy metals in seafood

Abstract: The aims of the present study were to obtain the seafood dietary patterns of coastal residents, to determine the concentrations of heavy metals, and to evaluate the possible health risks caused by seafood intake. The daily food intakes of 24 types of seafood were collected from 738 participants from Xiamen, a southern Chinese coastal city, using food frequency questionnaire (FFQ) and dietary history method. One hundred and fifty-six samples of 14 types of highest intake seafood were collected from local market… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…The Target Hazard Quotient (THQ) estimation methodology for human health risk assessment was initially proposed by the United States Environmental Protection Agency in the 1980s (USEPA 1989). The THQ is based on the calculation of metal concentrations in food, intake rates, and the reference oral dose, and has been used in studies evaluating the potential risk of exposure to contaminants in vegetables (Yañez et al 2018), vegetable oils (Zhu et al 2011), oysters (Zhao et al 2016), and fish (Yi et al 2011;Adel et al 2016;Avigliano et al 2016;Gu et al 2017). Because of the potential and/or real danger of consumption of fish with significant levels of toxic metals, many countries monitor the levels of these trace elements in fish locally consumed, to protect human health.…”
Section: Introductionmentioning
confidence: 99%
“…The Target Hazard Quotient (THQ) estimation methodology for human health risk assessment was initially proposed by the United States Environmental Protection Agency in the 1980s (USEPA 1989). The THQ is based on the calculation of metal concentrations in food, intake rates, and the reference oral dose, and has been used in studies evaluating the potential risk of exposure to contaminants in vegetables (Yañez et al 2018), vegetable oils (Zhu et al 2011), oysters (Zhao et al 2016), and fish (Yi et al 2011;Adel et al 2016;Avigliano et al 2016;Gu et al 2017). Because of the potential and/or real danger of consumption of fish with significant levels of toxic metals, many countries monitor the levels of these trace elements in fish locally consumed, to protect human health.…”
Section: Introductionmentioning
confidence: 99%
“…Among the polymicrobial infections, we found that EPEC and Vibrio presented the highest ratio (Additional file 6 : Table S3). One possible reason for this observation could be that the isolation rate of EPEC was the highest (24.6%), and Vibrio was the most frequently isolated pathogen from seawater and seafood, and the consumption of contaminated seafood appears to be one of the major causes of acute diarrhoea in Shanghai [ 49 ]. Finally, we noticed that the proportion of polymicrobial infections in the 20–39-year-old age group was significantly higher than that in the 40–59-year-old age group (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al [17] reported that some seafood from Xiangshan Bay might pose noncarcinogenic risks to both adults and children. Although consumption of most common types of seafood from Xiamen markets does not pose a noncarcinogenic risk, some types, such as yellowfin bream (Sparus latus), oyster, and the Red alga (nori; Porphyra tenera), could form a carcinogenic risk [18]. e levels of five metals in marine fish and shellfish from China are generally low, based on published data.…”
Section: Introductionmentioning
confidence: 99%